2022
DOI: 10.1111/codi.16133
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of colorectal cancer resection in patients with inflammatory bowel disease: a national population‐based analysis in England and Wales

Abstract: Aim:The aim was to compare early postoperative outcomes and 2-year cancer-specific mortality following colorectal cancer (CRC) resection in patients with and without inflammatory bowel disease (IBD) in England and Wales.Method: Records for patients in the National Bowel Cancer Audit who had major CRC resection between April 2014 and December 2017 were linked to routinely collected hospital level administrative datasets and chemotherapy and radiotherapy datasets.Multivariable regression models were used to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Another population-based analysis conducted by Birch et al showed that the patients with IBD-CRC were younger at cancer diagnosis (median; 66 vs. 72 years, p < 0.01), presented a tendency toward emergency cancer diagnosis (25.1% vs. 16.7%, p < 0.01), and had an increased prevalence of right-sided tumors (37.4% vs. 31.5%, p < 0.01) [ 4 ]. A recently conducted population-based study also demonstrated that patients with IBD-CRC had a significantly increased 2-year cancer-specific mortality rate compared to that of patients with sporadic CRC (HR, 1.35; 95% CI, 1.18–1.55) [ 78 ]. Lu et al conducted a systematic review and meta-analysis and reported that patients with IBD-CRC had significantly decreased overall survival (HR, 1.33; 95% CI, 1.20–1.47) and cancer-specific survival (HR, 2.17; 95% CI, 1.68–2.78) compared with those with sporadic CRC.…”
Section: Ibd-crc Prognosismentioning
confidence: 99%
“…Another population-based analysis conducted by Birch et al showed that the patients with IBD-CRC were younger at cancer diagnosis (median; 66 vs. 72 years, p < 0.01), presented a tendency toward emergency cancer diagnosis (25.1% vs. 16.7%, p < 0.01), and had an increased prevalence of right-sided tumors (37.4% vs. 31.5%, p < 0.01) [ 4 ]. A recently conducted population-based study also demonstrated that patients with IBD-CRC had a significantly increased 2-year cancer-specific mortality rate compared to that of patients with sporadic CRC (HR, 1.35; 95% CI, 1.18–1.55) [ 78 ]. Lu et al conducted a systematic review and meta-analysis and reported that patients with IBD-CRC had significantly decreased overall survival (HR, 1.33; 95% CI, 1.20–1.47) and cancer-specific survival (HR, 2.17; 95% CI, 1.68–2.78) compared with those with sporadic CRC.…”
Section: Ibd-crc Prognosismentioning
confidence: 99%
“…CRC patients typically have microsatellite stability/instability and exhibit long interspersed nuclear elements (LINE-1) hypomethylation and gene sequence variations, including TP53, KRAS, BRAF, and APC 6 8 . Currently, the treatment strategies for CRC mainly include neoadjuvant chemotherapy, surgical resection, and targeted therapy, which have favorable effects on CRC 9 11 . However, the death rate of CRC remains high for postoperative recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these mono-targeting strategy and due to long treatment durations, cancer cells can become less receptive to the administered drugs or even develop resistance (2,3), often leading to loss of control of the cancer disease. Thereby, inflammation and inflammatory processes are considered as the key drivers of health problems in many diseases, including chronic disorders such as rheumatoid arthritis (4), bowel diseases (5) as well as cancer (6). In general, acute inflammations can become chronic, consequently resulting in cell degeneration (7) development.…”
Section: Introductionmentioning
confidence: 99%